CHELLENGES IN TEACHING LISTENING TO YOUNG LEARNERS - Mamatqulov Ziyodbek Ilhom o’g’li Teshaboyeva Nafisa Zubaydulla qizi, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Teaching listening to young learners presents unique challenges due to their limited concentration span, diverse language proficiency levels, and the need for engaging and age-appropriate materials. Effective listening instruction requires tailored strategies, including interactive activities, use of visual aids, and repetition to enhance comprehension. Educators often encounter difficulties such as maintaining motivation, addressing learners with varying linguistic backgrounds, and creating a supportive environment for active listening. Overcoming these challenges involves incorporating multimodal resources, scaffolding techniques, and fostering a positive classroom atmosphere to develop young learners' listening skills effectively.